Is there a single surge mechanism? Contrasts in dynamics between glacier surges in Svalbard and other regions - Murray, Tavi; Strozzi, Tazio; Luckman, Adrian; Jiskoot, Hester; Christakos, Panos (American Geophysical Union, 2003)
Sherpa Romeo green journal. Permission to archive final published version. During the 1990s, Monacobreen, a 40-km-long tidewater glacier in Svalbard, underwent a major surge. We mapped the surge dynamics using ERS synthetic aperture radar images, differential dual-azimuth interferometry and intensity correlation tracking. A series of 11 three-dimensional (3-D) velocity maps covering the period 1991–1997 show a months-long initiation and years-long termination to the surge, with no indication of a surge front travelling downglacier. During the surge, the front of the glacier advanced 2 km, the velocity and derived strain rate increased by more than an order of magnitude, and maximum ice flow rates measured during 1994 were 5md 1. The spatial pattern of both velocity and strain rate was remarkably consistent and must therefore be controlled by spatially fixed processes operating at the glacier bed. We combine these results with those published in the literature to construct a typical Svalbard glacier surge cycle and compare this to surge dynamics of glaciers from other cluster regions, especially those of Variegated Glacier in Alaska. The strong contrast in dynamics suggests that there exist at least two distinct surge mechanisms. Yes